PENYITAAN BARANG BUKTI (BB) KASUS PENCURIAN YANG SUDAH DIJUAL PADA PENADAH BARANG SESUAI PUTUSAN PENGADILAN NEGERI NO.329/PID.B/2023/PN.KEPANJEN MALANG - Suryanto, Suryanto (Gapenas Publisher, 2025)
Theft in the family is an increasingly troubling problem in Indonesia, because the impact is not only material, but also deep psychological and social for the victim. This research is to find out what are the limits of Evidence that must be confiscated in the case of theft that has been sold in the sale of goods in accordance with District Court Decision No.329/Pid.Bid/2023/PN.Kepanjen Malang funds Ratio decidendi District Court Decision No.329/Pid.Bid/2023/PN.Kepanjen Malang which does not require confiscation of Evidence resulting from Money Laundering Crime. This legal research uses a normative juridical method with Doctrinal Research type, which is research sourced from applicable laws and regulations, court decisions, legal theories and concepts and the views of legal scholars. In a legal perspective, the application of Article 480 of the Criminal Code aims to have a deterrent effect on parties involved in the trade of stolen goods. The legal and social implications of this family theft case are significant. On the one hand, this case reminds the importance of the role of the family as the guardian of morals and values in society, while on the other hand, this case triggers the urgency of reforming the justice system and the mechanism of restoration to the family. The criminal liability of the perpetrators in this case shows that although family relationships should encourage mutual trust, in this case, this was the main reason why the victim placed trust in the perpetrator. Stolen goods committed by third parties, in this case gold shops, also need more serious attention from law enforcement officials because they help perpetrators disguise the proceeds of crime.